Human Rights Protection in Corporate Sector: A Legal Analysis - Winsherly Tan; Nurlaily Nurlaily; Shenti Agustini (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
This study examines the human rights protection in Indonesia’s business sector amid the rapid expansion of contemporary economic activities. Using a normative juridical method supported by statutory, conceptual, and theoretical approaches, the research analyzes the legal dynamics of human rights issues in corporate practices and the dilemmas that arise in their regulation. The findings show that the discourse on business and human rights has gained increasing prominence at global and national levels, encouraging Indonesia to adopt Presidential Regulation Number 60 of 2023 concerning the National Strategy on Business and Human Rights. Although this regulation provides a policy framework for promoting responsible business conduct, it still presents substantive limitations, particularly the absence of a designated independent institution to monitor corporate compliance. This institutional gap reduces the effectiveness of implementation and weakens the state’s capacity to ensure adequate human rights protection in the business environment. Therefore, this study recommends revising Presidential Regulation Number 60 of 2023 and appointing the National Human Rights Commission (Komnas HAM) as the independent supervisory body, in accordance with the mandate of Article 1 of Law Number 39 of 1999. Strengthening regulatory clarity and institutional oversight is essential to improving human rights protection in Indonesia’s business sector.